2021
DOI: 10.3390/ijerph18157739
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequalities in Children and Adolescents: A Scoping Review of the Mediating and Moderating Effects of Family Characteristics

Abstract: This scoping review systematically mapped evidence of the mediating and moderating effects of family characteristics on health inequalities in school-aged children and adolescents (6–18 years) in countries with developed economies in Europe and North America. We conducted a systematic scoping review following the PRISMA extension for Scoping Reviews recommendations. We searched the PubMed, PsycINFO and Scopus databases. Two reviewers independently screened titles, abstracts and full texts. Evidence was synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
(372 reference statements)
0
6
0
Order By: Relevance
“…To date, few studies have investigated whether health inequalities in adolescents are mediated by familial determinants [ 47 ]. A scoping review by Blume et al [ 47 ] revealed that parenting practices, parental mental health, as well as family conflict and distress, were relevant mediators for health inequalities in childhood and adolescence. Regarding mediation by familial determinants, a relatively large number of studies have examined mental health of young people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have investigated whether health inequalities in adolescents are mediated by familial determinants [ 47 ]. A scoping review by Blume et al [ 47 ] revealed that parenting practices, parental mental health, as well as family conflict and distress, were relevant mediators for health inequalities in childhood and adolescence. Regarding mediation by familial determinants, a relatively large number of studies have examined mental health of young people.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for other health outcomes (e.g., SRH), this issue has received relatively little investigation. Blume et al’s review [ 47 ] identified only three studies that explored whether the association between SEP and young people’s SRH was mediated by familial determinants [ 22 , 48 , 49 ]. Of the two studies that analyzed mediation through the parent-child relationship, one revealed a significant result [ 49 ] whereas the other found no mediating effect [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is that despite a large number of children attending day care facilities, this review focuses exclusively on the mediating and moderating effects of the family as the most important social environment in early childhood. The findings presented here should, therefore, be supplemented by reviews of cooperating research groups [ 68 ] on the effects of further relevant social environments, such as kindergartens [ 69 ] and schools [ 70 ], and by reviews examining late childhood and adolescence [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of parental investment may be as manifold as follows: behaviour (e.g., parent–child time spent, promotion of extracurricular activities), nutrition (e.g., sufficiently nutritious diets), education (e.g., learning materials available at home), health behaviour and health (e.g., utilization of medical care, parental health behaviour, rules restricting of media use), and living conditions (e.g., residence) [ 25 28 ]. The FIM and FSM reflect theoretical assumptions of family’s mechanisms underlying health inequalities, which only have been studied with regard to few health conditions among children [ 29 ]. However, in line with the assumptions of social causation (e.g., FSM, FIM), family characteristics could depend on the SEP which, in turn, affects children’s health (defining mediating effects).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research suggests upstream factors of health literacy may interact with each other and play different roles in child health literacy [ 89 , 90 ]. For example, family socioeconomic status has been found as a moderator in the relationship between health literacy and health outcomes such as health behaviours and health service use in the Irish population [ 90 ].…”
Section: Discussionmentioning
confidence: 99%